Prostate cancer disclosure and sexual orientation: Understanding outness to healthcare providers as a situational or consistent phenomenon. Issue 7 (July 2022) - Wells-Prado, Daniel R.; Ross, Michael W.; Rosser, B.R. Simon; Polter, Elizabeth J.; Capistrant, Bea D.; Haggart, Ryan; Kohli, Nidhi; Konety, Badrinath R.; Mitteldorf, Darryl; Talley, Kristine M.C.; West, William; Wheldon, Christopher W.
Highlights: Sexual orientation outness is situational in gay/bisexual prostate cancer survivors. Participants disclosed sexual orientation to their primary care provider the most. If out, surgeons and urologists were more likely to discuss sexual side effects. Sexual side effects among men who have sex with men were infrequently discussed. Abstract: Objective: In this study, we investigated if outness is more a situational or a consistent characteristic in gay, bisexual, and other men who have sex with men (GBM) treated for prostate cancer and how the disclosure of sexual orientation impacts provider discussions of sexual side effects. Methods: Data came from Restore, an online cross-sectional survey of 193 GBM prostate cancer survivors living in North America and were analyzed using various statistical models. Results: Disclosure of sexual orientation and of living with prostate cancer were not significantly correlated. Participants who were out regarding sexual orientation were more likely to report that their surgeons and urologists discussed the sexual side effects of treatment. Conclusion: Outness appears to be a situational phenomenon. GBM prostate cancer survivors who were out regarding sexual orientation received more discussion surrounding sexual side effects of prostate cancer treatment from their providers. Practice implications: It is important for healthcare providers to inquire about patient's sexual orientation to provide holistic care to these patients to address health disparities within this group.